2013
DOI: 10.1186/1471-2458-13-720
|View full text |Cite
|
Sign up to set email alerts
|

Active pulmonary tuberculosis and latent tuberculosis infection among homeless people in Seoul, South Korea: a cross-sectional study

Abstract: BackgroundThe aim of this study was to determine the prevalence rate of latent TB infection (LTBI) and active TB among homeless in Seoul metropolitan city, South Korea, and to compare the TB burden among homeless people with that of a control group.MethodsThe homeless participants were recruited from five sites between October 30, 2009 and April 12, 2010. LTBI was diagnosed through the QuantiFERON(R) TB Gold In-Tube(QFT-GIT) assay and a tuberculin skin test(TST) and, and active PTB was diagnosed based on chest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 20 publications
0
25
2
Order By: Relevance
“…Poverty has been suggested to be related to underweight status and malnutrition, which are known to be closely associated with the TB risk . Similarly, homeless people tend to have LTBI and active TB more frequently than their non‐homeless counterparts . However, adding the socioeconomic status to the model had no impact on the result in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…Poverty has been suggested to be related to underweight status and malnutrition, which are known to be closely associated with the TB risk . Similarly, homeless people tend to have LTBI and active TB more frequently than their non‐homeless counterparts . However, adding the socioeconomic status to the model had no impact on the result in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…Consequently, the risk of hospitalization due to infections (including TB) is higher in homeless persons than in the general population [11]. This is in line with a high prevalence of positive IGRA in homeless persons in Poland (36.7%), USA (12–40%), Japan (50.6%) and South Korea (75.9%) in non-outbreak settings [1216].…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies in other high-income countries (including Italy, Japan, South Korea and the USA) have reported latent tuberculosis infection prevalence in homeless populations and found rates varying from 16% to 75.9%. 5,[19][20][21][22] A meta-analysis of active tuberculosis and blood-borne virus prevalence in homeless populations internationally found that hepatitis C virus (HCV) infection ranged from 3.9% to 36.2%, and HIV infection ranged from 0.3% to 21.1%. 23 None of the studies testing for HIV was conducted in the UK, but one hepatitis C study, which recruited individuals experiencing homelessness from shelters, special projects and medical centres in Oxford, found 26.5% of individuals to be HCV infection positive using oral fluid testing.…”
Section: Discussionmentioning
confidence: 99%